Adolescents' expected civic participation: The role of civic knowledge and efficacy beliefs. Issue 5 (29th May 2014) - Manganelli, Sara; Lucidi, Fabio; Alivernini, Fabio
ABSTRACT: In the present study we examined the role of civic knowledge and efficacy beliefs as factors that can promote adolescents' expectations to participate in civic activities, while also taking into consideration the influences of socio‐economic background and gender differences. Structural equation modelling techniques were used to examine data from the International Civic and Citizenship Study, collected from 3352 eighth grade Italian students. Gender was found to significantly moderate some relationships between the variables, while efficacy beliefs, rather than civic knowledge, positively influenced expected civic participation. Socio‐economic background influenced all the variables included in the study, but it had a very small direct influence on adolescents' expected civic participation. It therefore appears that adolescents' expected civic participation can be encouraged by making them more confident about their civic and political abilities. These results extend our understanding of civic engagement in adolescents, and can inform policies aiming to promote it.